Effect of modified fibre flour wood on the fresh condition properties of cement-based mortars. (30th May 2019) - Aloulou, Fadhel; Alila, Sabrine
The effect of wood fibre flour in a studied Portland cement material shows interesting mechanical properties. The objective of this work is the elaboration new composite materials by emulsion. The dispersion of wood fibre and compressive strength was studied. The results showed an improvement in compressive strength of over 40% with 2% added wood fibres flour. The chemical modification of the wood fibres into their surfaces changes from the hydrophilic state to the hydrophobic state which makes it necessary to reduce the amount of water absorbed by the sample. The addition of anionic surfactant in the mixing water further improves the surface of the samples by minimising the pore size, hence the reduced water absorption. The dispersion of the wood fibres is controlled and assumed by an anionic surfactant as an emulsion phenomenon, the elaborate Maserati has thermal properties can be used as phase change materials (PCMs).